The mediating role of organizational commitment between workplace bullying and turnover intention among clinical nurses in China: a cross-sectional study - Guili Xia; Yi Zhang; Ling Dong; Fengtao Huang; Yao Pu; Jiang Luo; Yi-ping Chen; Zhengxia Lei (BMC, 2023)
Abstract Background Workplace bullying experienced by clinical nurses is a critical and pervasive issue that not only detrimentally impacts nurses but also poses a significant threat to the overall quality of nursing services and patient care. This study aimed to determine the mediating role of organizational commitment in the relationship between workplace bullying and turnover intention among clinical nurses in China. Methods Participants were recruited from 40 hospitals in various provinces of China from December 2, 2021 to February 25, 2023, using convenience sampling. After obtaining hospital ethical approval and participants' informed consent, clinical nurses (n = 585) from different nursing departments in different hospitals completed the questionnaire. The Socio-demographic Questionnaire, Negative Acts Qestionnaire, Chinese Workers' Organizational Commitment Scale and Turnover Intention Questionnaire were used to collect general demographic data of nurses and assess workplace bullying they experienced, their level of organizational commitment and turnover intention. Descriptive statistics, Pearson correlation analyses and structural equation model were adopted to analyze the data. Results Pearson's correlation analysis showed that that workplace bullying was significantly negatively correlated with organizational commitment (r = − 0.512, P<0.01) and significantly positively correlated with turnover intention (r = 0.558, P<0.01), organizational commitment was significantly negatively correlated with turnover intention (r = − 0.539, P<0.01). Mediation analysis indicated organizational commitment partially mediated the association between workplace bullying and turnover intention. The total effect (β = 0.69) of workplace bullying on turnover intention consisted of its direct effect (β = 0.41) and the indirect effect mediated through organizational commitment (β = 0.280), with the mediating effect accounting for 40.58% of the total effect. Conclusion Organizational commitment mediated the associations of workplace bullying and turnover intention. Therefore, healthcare organizations and nursing managers should develop appropriate strategies to enhance nurses' organizational commitment in order to reduce their turnover intention.